Locating the Kingdom of God performing sacred boundaries - Wenell, Karen J. ca. 21. Jh. (London New York Oxford New Delhi Sydney T&T Clark, 2024)
"This book provides a multidisciplinary approach to the study of the Kingdom of God, contributing new insights into the wider study of religion through close engagement with theory, texts, and ethical considerations."
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Kingdom of God